Anion and pH dependent molecular motion by a halogen bonding [2]rotaxane - Klein, HA; Kuhn, H; Beer, PD (Royal Society of Chemistry, 2019)
A bistable [2]rotaxane containing a halogen bonding benzimidazole–iodotriazole station directly conjugated to a naphthalimide station axle component is demonstrated to undergo macrocycle shuttling translocation only upon both protonation and chloride anion recognition. A naked-eye detectable colour response results from the co-conformational change of the host structure.